Azure for architects implementing cloud design, DevOps, containers, IoT, and serverless solutions on your public cloud - Modi, Ritesh (Packt, 2019)
Getting started -- Azure solution availability and scalability -- Security and monitoring -- Cross-subscription deployments using ARM templates -- ARM templates : modular design and implementation -- Designing and implementing serverless solutions -- Azure integration solutions -- Cost management -- Designing policies, locks, and tags -- Azure solutions using Azure container services -- Azure DevOps -- Azure OLTP solutions using Azure SQL sharding, pools, and hybrid -- Azure big data solutions using Azure data lake storage and data factory -- Azure stream analytics and event hubs -- Designing IoT solutions
Includes index
Keywords: Windows Azure; Cloud computing; Architecture / Data processing